2020
DOI: 10.1186/s12891-019-3036-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for subsidence of titanium mesh cage following single-level anterior cervical corpectomy and fusion

Abstract: Background: To clarify the risk factors for subsidence of titanium mesh cage (TMC) following single-level anterior cervical corpectomy and fusion (ACCF) to reduce subsidence. Methods: The present retrospective cohort study included 73 consecutive patients who underwent single-level ACCF. Patients were divided into subsidence (n = 31) and non-subsidence groups (n = 42). Medical records and radiological parameters such as age, sex, operation level, segmental angle (SA), cervical sagittal angle (CSA), height of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 26 publications
2
70
0
Order By: Relevance
“…Cage subsidence occurred in 67.9% (19/28) and appeared before 6 months after the operation, while all patients achieved solid fusion at final follow-up, which is consistent with the results of previous studies. 37,47,48 Although internal fixation failure is common in cage subsidence with osteoporosis, it did not occur in our research. The outstanding result may be related to the use of a long segmental bone cement screw technique.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Cage subsidence occurred in 67.9% (19/28) and appeared before 6 months after the operation, while all patients achieved solid fusion at final follow-up, which is consistent with the results of previous studies. 37,47,48 Although internal fixation failure is common in cage subsidence with osteoporosis, it did not occur in our research. The outstanding result may be related to the use of a long segmental bone cement screw technique.…”
Section: Discussionmentioning
confidence: 50%
“… 28 , 36 The subsidence has been proven to correlate with osteoporosis, progressive resection of the endplate, a sharp edge of mesh, or over intervertebral distraction. 37–40 From June 2016, 12 consecutive patients with KD underwent anterior reconstruction with the 3D-AVB were involved in our center and compared with the previous 16 consecutive patients who restoration with the TMC. Our study showed that the subsidence was less with the group of 3DP-AVB than the TMC group (average, 0.97 mm vs 5.39 mm) and a lower risk of severe subsidence in the 3DP-AVB group (8.3% vs 50%, P <0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to reports, the incidence of implant-related complications is from 14.3 to 21.6% in anterior reconstruction surgery for Kümmell’s disease [ 26 ] and cage subsidence is an important risk factor related to the instrumentation failure [ 27 ]. In the past few years, 3D printed artificial vertebral body with good implant fit and less subsidence has gained traction in spine surgery [ 28 30 ] and the excellent result may attribute to the following aspects: (1) a larger diameter endcap of 3D prosthesis allows for an expansion of the bone-implant interface, which distributes point-loading and loads the periphery of the endplates where there is thicker cortical bone, and eventually reduces the risk of subsidence [ 29 , 31 ]; (2) with a Young‘s modulus more similar to native human bone (0.5–20 GPa), may reduce subsidence and ‘stress shadowing effect’ compared with traditional implants [ 32 ]; (3) the porosity of 3D vertebral body made by Ti6-Al4-V titanium alloy can enhance the delivery of osteoinductive factors as well as facilitate osteoconduction, thus potentially improving bony ingrowth [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…TMC subsidence may be correlated with poor clinical e cacy or poor neurological recovery. Severe subsidence will lead to symptom recurrence, deterioration of nerve function, failure of internal xation and kyphosis of the cervical spine [13,14]. There are many risk factors related to TMC subsidence, among which patients' own conditions and operation reasons can be avoided by case screening and operation technology improvements.…”
Section: Introductionmentioning
confidence: 99%